Revisión documental sobre la influencia del consumo de alcohol en la comisión del delito de homicidio entre 2015 y 2020 (2021)
This research addressed the influence of alcohol consumption on the criminal behavior of homicide in early adulthood, where the main risk factors associated with this criminal behavior were identified. depending on biological, psychological, social factors among others that influence the development of these variables of alcohol and homicide; since the magnitude of the problem was evidenced through global statistics identifying high rates of alcohol consumption and homicide in the different countries of Latin America, through the problem aims to identify the main psychological affectations that occur; through this documentary review based on articles between 2015 and 2020 from Colombia, where the main causes that affected violent or aggressive behaviors were identified, which directly or indirectly affect the life of a person for both internal and external causes in the various population contexts.